2018
DOI: 10.1136/jech-2017-210171
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational social mobility and allostatic load in Great Britain

Abstract: BackgroundIntergenerational social mobility is hypothesised to be a stressful process that has a negative effect on health. By examining the relationship between own socioeconomic position, parental socioeconomic position and allostatic load (AL) in a representative sample of the British population, we test this hypothesis.MethodsOur study uses cross-sectional data from 9851 adult participants of waves 2 and 3 of Understanding Society. The relationship between parental occupational class at age 14 years, respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 36 publications
7
38
0
Order By: Relevance
“…There are two main inferences from these findings. First, not only does an individual's own socio-economic status relate to arts engagement, as previously shown, but our findings suggest that the effects of socio-economic status on participation may transfer into the next generation (as also shown in academic achievement [39] and health outcomes [47]. It is possible that this is because factors such as wealth mean that some families are less able to pay for activities for their children.…”
Section: Discussionsupporting
confidence: 58%
“…There are two main inferences from these findings. First, not only does an individual's own socio-economic status relate to arts engagement, as previously shown, but our findings suggest that the effects of socio-economic status on participation may transfer into the next generation (as also shown in academic achievement [39] and health outcomes [47]. It is possible that this is because factors such as wealth mean that some families are less able to pay for activities for their children.…”
Section: Discussionsupporting
confidence: 58%
“…There are other studies that have focused on social class, mobility, and broader political attitudes but findings regarding the role played by intergenerational loss are mixed (Breen, 2001;De Graaf et al, 1995;Jaime-Castillo and Marqués-Perales, 2019;Paterson, 2008). Several studies have looked at whether downward social mobility is associated with lower well-being or life satisfaction, however, there is no consensus on this question either (Becker and Birkelbach, 2018;Hadjar and Samuel, 2015;Kaiser and Trinh, 2019;Präg and Richards, 2019;Zhao et al, 2017). In this study, we add to this literature by studying the relationship between intergenerational social mobility and attitudes towards immigrants.…”
Section: Intergenerational Loss and Attitudes Towards Immigrants: Micro-mechanismsmentioning
confidence: 99%
“…A handful of studies have examined the association of SEP with AL over the life course (Gustafsson et al, 2011;Gruenewald et al, 2012;Robertson et al, 2014;Solis et al, 2016;Prag and Richards, 2018). Comparison of results across studies is complicated by the fact that AL is not always measured using the same number or composition of biomarkers, but most of them have concluded that the socio-economic conditions of childhood and adulthood have separable and additive effects on AL.…”
Section: Allostatic Loadmentioning
confidence: 99%